Love, medicine & miracles - Siegel, Bernie S. (New York : Harper & Row Publishers, Inc, 1986)
Explores the link between mind and body, and shows how to become a survivor.
Includes bibliographical references (p. 235-239).
Wilson's Public Library
Adult.
Adult
Keywords: Attitude to Health -- popular works; Love -- Psychological aspects; Love -- Psychological aspects; Medicine and psychology; Medicine; Mind and body; Mind and body; Neoplasms -- psychology -- popular works; Psychology; Psychophysiology -- popular works; Self Care -- psychology -- popular works